Pengaruh Mental Workload, Stress Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Nutrisius Sari Persada - Herdiana Herdiana; Imal Istimal (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The purpose of this study was to analyze the effect of mental workload on employee performance, the effect of work stress on employee performance, the work environment on employee performance and to analyze the effect of mental workload, work stress, and work environment simultaneously on the performance of employees of PT. Nutrisius Sari Persada. This research design uses quantitative methods with an associative approach and data collection techniques of library research and field research. Data analysis techniques using descriptive statistical analysis techniques using data processing tools Structural Equation Modeling (SEM) with SmartPLS software by testing mental workload variables (X1), work stress (X2), work environment (X3) and employee performance (Y). The results of this study indicate that the mental workload variable (X1) on employee performance (Y) has a T-test value of (2.013> 1.96) and P values of (0.045 < 0.05), the work stress variable (X2) has a T-test value of (10.237> 1.96) and P values of (0, 000 < 0.05), the work environment variable (X3) has a T-test value of (2.013> 1.96) and P values of (0.045 < 0.05), so it can be concluded that the mental workload variable (X1), work stress (X2) and the work environment (X3) have an influence on employee performance (Y). While simultaneously mental workload (X1), work stress (X2) and work environment (X3) variables on employee performance (Y). The results of the analysis of the coefficient of determination (R2) obtained a value (Adjusted Rsquare) of 0.973, meaning that all independent variables are declared strong with a value of 97% and the remaining 3% is influenced by other variables outside the Mental Workload, Work Stress and Work Environment variables.